Mathcad® - a 'learning enabler' in power electronics education - Kennedy, Robert T.; Tunku Muhamad Nizar, Tunku Mansur; Ismail, Daut (Association of Engineering Education in South East Asia and the Pacific, 2008)
Organized by Association of Engineering Education in South East Asia and the Pacific, 14th February 2007 at Kuala Lumpur, Malaysia.